Painters of Lubumbashi : Bela - Pili Pili - Mwenze. (Kinshasa : Galerie privée Louis van Bever, 1992)
Bela ; Pili Pili ; Mwenze
Painters of Lubumbashi : Bela - Pili Pili - Mwenze, European Centre for Development Policy Management, Maastricht, 30 June - 28 August 1992
boek